CAPITAL STRUCTURE AND PROFITABILITY INFLUENCING FIRM VALUE MODERATED BY FIRM SIZE - Fernanda, Vira; Yanti, Yanti; Sastrsasmita, Emillia (Graduate Program of Universitas Tarumanagara, 2025)
This study aims to analyze the influence of capital structure and profitability on firm value moderated by firm size. The sample was selected using purposive sampling resulting in 38 companies out of 58 listed on the Indonesia Stock Exchange (IDX) with three years of observation (2020-2022) as the objects of this research. Moreover, the hypothesis testing method in this study uses a panel data regression model using Eviews program version 12 to analyze the model. The results of this research show that capital structure influences firm value positively. However, profitability does not affect the firm value. Meanwhile, the moderated research shows that firm size is unable to moderate both the influence of capital structure and profitability on firm value.